Overhead Transmission Line Modeling Strategies for EMT-Based Traveling-Wave Analysis and Fault Location - Adrian Wilmer Diaz Sarmiento; Jaimis Sajid Leon Colqui; Jose Pissolato Filho (IEEE Access)
This paper presents a systematic evaluation of overhead transmission line (OHTL) modeling approaches for traveling-wave (TW)–based fault analysis in power systems. The study examines five critical modeling aspects: soil resistivity representation, shield wire inclusion and Kron reduction, modal decomposition techniques, fault location accuracy, and tower grounding representation. Comprehensive electromagnetic transient (EMT) simulations of a 220 kV, 330 km OHTL were performed using the Carson and Pettersson formulations to calculate electrical parameters, both with and without considering the frequency dependence of ground parameters. The results show that: 1) uniform soil resistivity assumptions introduce negligible errors in TW arrival times despite minor amplitude variations; 2) shield wires significantly affect modal structure, compromising the effectiveness of Clarke transformation for ground quasi-mode decoupling while preserving aerial quasi-mode reliability; 3) exact eigenvector-based decomposition improves ground mode identification but remains impractical for field applications; 4) the classical two-terminal fault location method maintains high accuracy across all modeling configurations; and 5) simplified OHTL modeling uniformly distributed sections at both terminals achieves an optimal balance between accuracy and computational efficiency for simulating TWs. These findings provide practical guidelines for EMT simulations and TW-based fault location schemes, particularly regarding appropriate model simplification.